Maternal type 1collagen N-terminal telopeptide levels in severe hyperemesis gravidarum - E. Sahin (BMC Pregnancy and Childbirth, 2018)
Abstract Background Nausea and vomiting occur 50–90% during the first trimester of pregnancy. However, patients with hyperemesis gravidarum (HG) may be hospitalized at an incidence rate of 0.8–2% before the 20th week of gestational age. The symptoms generally start during the 5–6th gestational weeks, reaching the highest degree during the 9th week, and decline after the 16–20th weeks of gestation. Clinical findings are proportional to the severity of the disease and severe HG is characterized with dehydration, electrolyte imbalance, and nutritional deficiency as a result of vomiting. Methods The study population consisted of two groups of pregnant volunteers at 5–12 weeks of gestation: a severe HG group and a control group. The HG severity was scored using the Pregnancy-Unique Quantification of Emesis (and nausea) (PUQE).The serum levels of the maternal Ca, parathyroid hormone (PTH), Na, K, blood urea nitrogen(BUN), creatinine, vitamin D(25OHD3), and the maternal urine NTx levels were compared between the groups. Results In total, 40 volunteers were enrolled in this study: 20 healthy pregnant volunteers and 20 with severe HG. There were no statistically significant differences between the maternal characteristics. The first trimester weight loss of ≥5 kg was significantly higher in the severe HG group (p < 0.001), while the control group had a significantly higher sunlight exposure ratio than the severe HG group (p = 0.021). The urine NTx levels were significantly higher in the severe HG group (39.22 ± 11.68NTx/Cre) than in the control group(32.89 ± 8.33NTx/Cre) (p = 0.028).The serum Ca, PTH, Na, K, BUN, and creatinine levels were similar between the groups (p = 0.738, p = 0.886, p = 0.841, p = 0.957, p = 0.892, and p = 0.824, respectively). In the severe HG group, the serum 25OHD3 levels were significantly lower than in the control group (p < 0.001). Conclusions The data from this study indicated that severe HG is associated with increased urine NTx levels. However, large-scale studies are required to understand the clinical significance of this finding, as well as the long-term consequences of elevated urine NTx levels and the underlying mechanisms. Trial registration NCT02862496 Date of registration: 21/07/2016.